The association between day of delivery and obstetric outcomes: an observational study - Palmer,WL; Bottle,A; Aylin,PP (The BMJ, 2015)
Objective To examine the association between day of delivery and measures of quality and safety of maternity services and, in particular, compare weekend with weekday performance.Design We examined outcomes for maternal and neonatal records within the nationwide administrative dataset for English hospitals by day of the week. Groups were defined by day of admission (for maternal indicators) or delivery (for neonatal indicators) rather than by day of complication. We used logistic regression to adjust for case-mix factors including gestational age, birth-weight, and maternal age. We also investigated staffing factors using multi-level models to evaluate the association between outcomes and level of consultant presence. Setting English National Health Service public hospitals.Participants 1,332,835 deliveries and 1,349,599 births between 1 April 2010 and 31 March 2012. Main outcome measures The primary outcomes were perinatal mortality and – for both neonate and mother – infections, emergency readmissions and injuries.Results Performance across four of the seven measures was significantly worse for women admitted, and babies born, at weekends. In particular, the perinatal mortality rate was 7.3 per 1,000 babies delivered at weekends, 0.9 per 1,000 higher than at weekdays (adjusted odds ratio [AOR] 1.07; 95% confidence interval 1.02 to 1.13). We did not identify a consistent association between outcomes and staffing, although trusts who complied with recommended levels of consultant presence had a perineal tear rate of 3.0% compared with 3.3% for non-compliant services (AOR 1.21; 1.00 to 1.45).Conclusion The study suggests an association between day of delivery and aspects of performance, and some outcomes appear worse for both women admitted, and babies born, at the weekend. The results would suggest approximately 770 perinatal deaths and 470 maternal infections per year above what might be expected if performance was consistent across women admitted, and